2006
DOI: 10.1111/j.1467-789x.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐carbohydrate diets: nutritional and physiological aspects

Abstract: Recently, diets low in carbohydrate content have become a matter of international attention because of the WHO recommendations to reduce the overall consumption of sugars and rapidly digestible starches. One of the common metabolic changes assumed to take place when a person follows a low-carbohydrate diet is ketosis. Low-carbohydrate intakes result in a reduction of the circulating insulin level, which promotes high level of circulating fatty acids, used for oxidation and production of ketone bodies. It is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 63 publications
4
152
0
5
Order By: Relevance
“…HP diets tend to have reduced carbohydrate content, in the form of fruits, vegetables (if starchy foods are not adequately replaced by other types of low-carbohydratecontaining vegetables) and grains. This may theoretically place an individual at an increased disease risk if such a diet is followed long term, and fruit and vegetable intakes remain low (90) . HP dieting is associated with increased consumption of meat, and red meat consumption has been linked to colorectal cancer (91) , but the evidence is not straightforward.…”
Section: Gut Healthmentioning
confidence: 99%
“…HP diets tend to have reduced carbohydrate content, in the form of fruits, vegetables (if starchy foods are not adequately replaced by other types of low-carbohydratecontaining vegetables) and grains. This may theoretically place an individual at an increased disease risk if such a diet is followed long term, and fruit and vegetable intakes remain low (90) . HP dieting is associated with increased consumption of meat, and red meat consumption has been linked to colorectal cancer (91) , but the evidence is not straightforward.…”
Section: Gut Healthmentioning
confidence: 99%
“…On the other hand, a high-GI diet could conversely result in high postprandial insulin so blood glucose might rapidly decrease with an increase in counter-regulatory hormones causing declining insulin sensitivity (25). In addition, the high-GI diet also results in increasing lipid accumulation in skeletal muscle and liver which may cause insulin signaling defects and insulin resistance, and triacylglycerol accumulation in β cells also leads to decreased insulin secretion (23,26,27).…”
Section: Articlesmentioning
confidence: 99%
“…On the other hand, a high-GI diet could conversely result in high postprandial insulin so blood glucose might rapidly decrease with an increase in counter-regulatory hormones causing declining insulin sensitivity (25). In addition, the high-GI diet also results in increasing lipid accumulation in skeletal muscle and liver which may cause insulin signaling defects and insulin resistance, and triacylglycerol accumulation in β cells also leads to decreased insulin secretion (23,26,27).Due to the difference of baseline insulin levels between the two groups, we did general linear model and multiple regression analysis to adjust for the difference of baseline fasting plasma glucose, insulin, and HOMA-IR. The baseline fasting plasma glucose, insulin, and HOMA-IR had a greater effect on the mean difference of these results compared with the type of treatments.…”
mentioning
confidence: 99%
“…Analysis of the macronutrient composition of the diet has shown that individuals with SCI typically consume a diet that provides more than 30% of their total daily energy intake from fat (25,82,83). Although there is no consensus on the optimal macronutrient composition of the diet for weight loss or the role of dietary fat in the development of obesity (84,85), consumption of a diet low in fat can help with weight loss because it can be part of a lower caloric density diet, which encourages the consumption of high fiber foods that foster satiety and are compatible with diets advised for overall health (86)(87)(88). In the only published weight loss intervention study, caloric-restricted diets of 1,400 calories for men and 1,200 calories for women were used, but information on the macronutrient composition of the prescribed regimen was not provided (23).…”
Section: Management Treatmentmentioning
confidence: 99%